Effectiveness of Asthma Inhaler Pharmacotherapy must take into consideration both the device and drug and which is guided by clinically meaningful outcomes - Elissa M McDonald; Felix SF Ram (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
Introduction: The  inhalation  route  remains  the  mainstay  of  therapy  for asthma  and  chronic obstructive  pulmonary  disease  (COPD). This confers  a  number  of  advantages  such  as  delivery  of medication  directly  to  the site of  action  resulting  in  faster onset. It also allows  smaller  doses  to  be  administered  and therefore significantly reduces systemic side effects compared with oral therapy. The drug treatment regime for the majority of patients  with  asthma  and  COPD is straightforward and is documented in many guidelines [1-3]. However, the choice of which inhaler device to use is less straightforward. Rather than being spoilt for choice, we are frequently confused by the ever-increasing  number  of  devices  available.  Although  inhalation therapy  is  now  the  mainstay  of  asthma  treatment,  for  most patients  such  treatment  is  still  not  optimal.